2020
DOI: 10.3758/s13421-020-01030-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental change in partition dependent resource allocation behavior

Abstract: Partition dependence, the tendency to distribute choices differently based on the way options are grouped, has important implications for decision making. This phenomenon, observed in adults across a variety of contexts such as allocating resources or making selections from a menu of items, can bias decision makers toward some choices and away from others. Only one study to date (Reichelson, Zax, Patalano, & Barth, 2019) has investigated the developmental trajectory of this phenomenon. In the current study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Affect-as-information theory (Clore et al , 2001) and partition dependence theory (Williams et al , 2020) motivate the hypotheses of this study. Nonprofessional investors are likely to rely on their affective reactions to the tone of the details describing the ICFR in their evaluation of the company (Elliott et al , 2013).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Affect-as-information theory (Clore et al , 2001) and partition dependence theory (Williams et al , 2020) motivate the hypotheses of this study. Nonprofessional investors are likely to rely on their affective reactions to the tone of the details describing the ICFR in their evaluation of the company (Elliott et al , 2013).…”
Section: Introductionmentioning
confidence: 93%
“…The effect predicted in H1 is likely mediated by the negative tone’s impact on investors’ perceptions of the individual parts of the material weakness. Partition dependence theory suggests that a person’s evaluation of an event is dependent on how an event space is divided up and that people tend to automatically adopt the event space with which they are presented (Williams et al , 2020). For example, Xing et al (2020) found that students’ allocation of financial aid to income groups depended on how the income groups were divided insomuch that students allocated more financial aid to the below $75,000 income group when that group was presented with more distinct income categories than when that income group was only presented as a single category.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%